Perbandingan Sumber Pendapatan Negara Menurut Perspektif Abu Ubaid dan Sistem APBN Indonesia - Ali Akhmadi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This study investigates the comparative dynamics of state revenue sources between Abu Ubaid’s Kitab al-Amwal and the Indonesian State Budget (APBN) framework. Utilizing a qualitative library research design with a descriptive-comparative approach and content analysis, the research delineates the structural evolution of fiscal justice from classical paradigms to contemporary regulations. The findings reveal a profound philosophical convergence centered on maslahah (public interest), where the state serves as a fiduciary entity for the equitable redistribution of wealth. Technically, classical instruments such as kharaj and ushr demonstrate functional equivalence to Indonesia’s Land and Building Tax (PBB) and Customs. However, a distinct ontological divergence persists: Abu Ubaid’s model is anchored in a static, theocentric-ethical foundation, whereas the APBN operates within a dynamic, anthropocentric-technocratic constitutional structure. A pivotal insight of this study identifies Abu Ubaid’s mandate for "protecting the production base" as a critical moral critique of aggressive tax ratio targets that jeopardize public purchasing power. The research concludes that synthesizing classical economic ethics with modern fiscal administration is imperative to bolster the moral legitimacy of state policies, ultimately fostering more inclusive and sustainable social justice.